BLOOD METABOLITES OF BUFFALOES WITH DIFFERENTIAL FERTILITY UNDER UNIFORM FEEDING - DADARWAL, D; GHUMAN, S P S; SINGH, JAGIR; HONPARKHE, M; DHALIWAL, G S; MEHRA, M L (The Indian Journal of Animal Reproduction, 2023)
The present study was conducted on 18 anestrus (nulliparous, n=12; pluriparous, n=6) and 12cycling (nulliparous, n=?; pluriparous, n=5) buffaloes that were blood sampled three times at weeklyinterval. Plasma samples were analyzed for glucose, total proteins, albumin, urea, creatinine, lipidprofile, AST, ALT, LDH, Ca and P. This study reveals that none of the blood metabolites were differentbetween anestrus or cycling nulliparous buffaloes. However, cycling pluriparous buffaloes had higher(p
Keywords: Anestrus; Blood metabolites; Buffalo; Nutrition